Dentists' Practices and Attitudes Toward Using Personal Protection Equipment and Associated Drawbacks and Cost Implications During the COVID-19 Pandemic - Chasib, Nibras H.; Alshami, Muhanad L.; Gul, Sarhang S.; Abdulbaqi, Hayder R.; Abdulkareem, Ali A.; Al-Khdairy, Salah A. (Frontiers in Public Health, 2021)
Objectives: During the Covid-19 pandemic, dentists have had to work under stressful conditions due to the nature of their work. Personal protection equipment (PPE) has become mandatory for work in the dentistry field. This study aimed to examine dentists’ knowledge and attitudes regarding the use of PPE and the associated drawbacks and cost implications during the pandemic. Methods: A questionnaire-based survey was used and was divided into five sections dedicated to collect demographic variables and to examine the dentists’ knowledge, attitudes toward PPE, drawbacks, and cost of using PPE. Mann-Whitney U and Kruskal-Wallis tests were used to compare different sections of the questionnaire and linear regression was used to determine the predictors of the dentists’ knowledge and attitudes towards PPE. Results: The mean of knowledge regarding use of PPE was 5.41 ± 1.71 (median 6), attitude towards using PPE scored 2.26 ± 0.90 (median 2), while the means of drawbacks and cost recorded equal scores of 5.22 ± 1.24 (median 5) and 1.68 ± 0.74 (median 2), respectively. The recently graduated dentists, those with postgraduate degrees and those working in the private sector demonstrated higher levels of knowledge on PPE than their counterparts. Regression analysis revealed that knowledge of PPE can be predicted on the basis of qualifications and work place, whereas attitude toward PPE is significantly influenced by qualification only. Conclusions: The study participants demonstrated satisfactory levels of knowledge and positive attitudes toward PPE. While complaints from using PPE and their cost were moderately affected.